Power Politics in the Structure of Indonesian Democracy as a Manifestation of the Relationship between State Interests and Elite Domination - Jerry Sambuaga (International Journal of Education, Vocational and Social Science, 2026)
Power relations constitute a central dimension in understanding the dynamics of democracy, particularly in countries where political institutions coexist with strong elite influence. This article examines power politics within the structure of Indonesian democracy as a manifestation of the relationship between state interests and elite domination. The study aims to analyze how political and economic elites shape public policy and influence the decision-making process within democratic institutions. Using a qualitative approach with a normative and analytical perspective, this research explores the interaction between political authority, economic power, and institutional governance in Indonesia’s contemporary democratic system. The findings indicate that although Indonesia has adopted formal democratic procedures such as competitive elections and institutional checks and balances, the concentration of power among a limited group of political and economic elites continues to influence the direction of policy formulation. This condition reflects the persistence of oligarchic tendencies in democratic governance, where state interests are often intertwined with the strategic interests of dominant elites. As a result, public policies may not always fully represent broader societal aspirations but instead reflect negotiated outcomes among powerful actors within the political system. The study argues that the consolidation of democracy in Indonesia requires stronger institutional accountability, transparency in policy making, and broader public participation to reduce the excessive influence of elite domination. Strengthening democratic institutions and regulatory frameworks is therefore essential to ensure that state policies truly reflect the public interest rather than narrow elite agendas.